2017
DOI: 10.1508/cytologia.82.83
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic of Skink (Reptilia, Scincidae) from Thailand: II: Chromosome Analyses of Stripe Tree Skink (<i>Lipinia vittigera</i>)

Abstract: Chromosomal analyses of the stripe tree skink (Lipinia vittigera Boulenger, 1894) from mitotic and meiotic cell divisions were studied. Bone marrow and testis samples were taken from five male and five female skinks. Skink chromosome preparations were conducted by squash technique from bone marrow and testis. The chromosomes were stained by conventional staining and Ag-NOR banding techniques. The results showed that the diploid chromosome number of L. vittigera was 2n=28, and the fundamental number (NF) was 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Chromosomes were prepared using bone marrow and testes tissue, respectively, following the method of Patawang et al [ 7 ] and Wang et al [ 17 ]. The slides were routinely stained for 30 min using 10% Giemsa’s solution [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromosomes were prepared using bone marrow and testes tissue, respectively, following the method of Patawang et al [ 7 ] and Wang et al [ 17 ]. The slides were routinely stained for 30 min using 10% Giemsa’s solution [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are about 1760 species of skinks, accounting for 15% of the reptile species diversity [ 6 ]. They vary in chromosome number from 2n = 22 to 2n = 36, include both macrochromosomes and microchromosomes [ 5 , 7 , 8 ], and show genus conservation [ 8 , 9 , 10 ]. Many careful cytogenetic studies on skinks were conducted in the past, but sex chromosomes were rarely identified [ 8 ], and only 39 species have been reported with sex chromosomes to date [ 3 , 5 , 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern Thailand consists of the narrow Kra Isthmus, which widens into the Malay Peninsula. Professor Tanomtong and his coworkers are currently analyzing karyotypes of several species in these regions, including Rhinolophus coelophyllus; R. pusillus (Patawang et al 2017c); Axis (Khongcharoensuk et al 2017); Varanus bengalensis Tanomtong 2017, Patawang et al 2017a); Lipinia vittigera (Patawang, et al 2017b); Microhylid spp. (Sangpakdee et al 2017); Hoplobatrachus rugulosus (Tengjaroenkul et al 2017); the three-spot damselfish Dascyllus trimaculatus (Getlekha et al 2017); the tropical oyster Crassostera belcheri (Chooseangjaew et al 2017); freshwater fish, such as Nile tilapia, Oreochromis niloticus (Sriuttha et al 2017); freshwater perciforms Channa marulius and C. marulioides (Sarasan et al 2018); the hihgfin barb fish, Cyclocheilichthys armatus (Chaiyasan et al 2018); and the black lancer, Bagrichthys majusculus (Supiwong et al 2018).…”
Section: Thailand Including the Indochina And Northern Malay Peninsulasmentioning
confidence: 99%
“…Currently, about 8% of scincid species have been karyotyped (Greer and Shea, 2000;Olmo and Signorino, 2005;Kaewsri et al, 2014;Kostmann et al, 2021). The diploid chromosome numbers in this family range from 2n = 22 to 2n = 36 (Giovannotti et al, 2010;Patawang, 2017). Karyological analyses were conducted on four species of lizards collected from Semnan Province of Iran in 2010 (Table 1).…”
mentioning
confidence: 99%